CYDNIDAE (HEMIPTERA) COLETADOS EM ARMADILHA LUMINOSA EM SANTA MARIA, RS - Link, Dionisio (REVISTA DE AGRICULTURA, 2015)
CYDNIDAE (HEMIPTERA) COLETADOS EM ARMADILHA LUMINOSA EM SANTA MARIA, RS R ASPERSÃƒO